(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2024)
The work environment significantly impacts employee relationships and workplace dynamics. A positive environment promotes collaboration, teamwork, job satisfaction, and recognition, while a negative one can led to tension and disengagement. Open communication, well-organized spaces, diverse environments, and opportunities for personal and professional growth strengthen bonds. This research paper explores the relationship between bullying at work place and burnout through psychological stress and the buffering effect of perceived organizational support. Study provides a comprehensive understanding of the mechanisms through which bullying at work place effects employee burnout and explores the potential protective role of perceived organizational support in alleviating burnout symptoms. This study works on a quantitative research methodology and collects data from employees working in miscellaneous industries. Questionnaire has been circulated via online mode and through google form to 300 employees from numerous industrial sectors. The findings indicate positive association between bullying at workplace and burnout signifying that those individuals who are working in such organizations or those who have experienced bullying at work place leave the organization at its earliest.